Reliability, maintainability, and supportability : best practices for systems engineers - Tortorella, Michael, 1947- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
"Provides exercises in each chapter, allowing the reader to try out some of the ideas and procedures presented in the chapter"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Reliability (Engineering); TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Industrial Engineering; Reliability (Engineering); Electronic books; Electronic books